Profitability of Insurance Brokerage Firms in Ghana - Franklin Owusu-Sekyere; Richard Angelous Kotey (Academic Journal of Economic Studies, 2019)
The financial industry is growing up rapidly, enabling large volumes of transactions to be carried out. This growth has significantly increased the demand for insurance and insurance products. Though prior studies have examined the factors that drive the performance of the insurance industry from life and non-life perspective, not much attention had been given to the contribution of insurance brokers who perform key roles in the insurance sector. This study examined the factors that determine the profitability of insurance brokers in a developing economy, Ghana. Panel data from 64 insurance brokerage firms were sampled over a period of 5 years (2011 to 2015). The study adopted a fixed effects and random effects estimation model using robust standard errors to check for biases. We found that monetary assets and firm size positively affects returns (ROA and ROE) whilst debt and fixed assets had a negative effect on returns. Comparing monetary assets and size, size contributed more to profitability. The study recommends that government, policymakers, and other stakeholders adopt competent growth and development strategies to ensure the sector is more resourced.
Keywords: G22; G24; L25; 330; Profitability; Performance; Insurance; Brokerage